Teaching Vocabulary Through Picture Cards in Islamic Elementary School A Case Study in Nida Suksa School, Thailand - Octaberlina, Like Raskova; Anggarini, Ida Fitri (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2020)
Abstract. Nowdays, english as a subject learned in primary school level. Its because the important of english towards the student. This study was conducted aimed to know the influence of Picture Cards in teaching vocabulary to the third grade of Nida Suksa School, Thailand. The subjects of the research were students in the third grade. The researcher only took nine students in different abilities from a high level (3/1), middle level (3/2), and low level (3/3). The instrument used by the researcher was an interview. The result showed that the students still had difficulty in understanding the texts because of having a lack of vocabulary, long texts, and limited time to analyze the text in answering the question. The students studied vocabulary through Picture Cards, and they learned vocabulary tests from text book. Furthermore, the finding of this study was: Picture Cards is able to increase and enrich their vocabulary and their knowledge. The implication of Pictures Cards can motivate students to understand the text. Therefore, they can understand many texts in vocabulary tests.Keywords: Teaching Vocabulary, Picture CardsÂ